1994
DOI: 10.1007/s004410050230
|View full text |Cite
|
Sign up to set email alerts
|

The neurite growth promoting protease nexin 1 in glial cells of the olfactory bulb of the gerbil: an ultrastructural study

Abstract: The glia-derived serine protease inhibitor and neurite outgrowth promoter protease nexin-1 (PN-1) is expressed in Schwann cell precursors and astroblasts during embryogenesis. In the adult nervous system, PN-1 persists in the Schwann cells and olfactory glia only. Light-microscopic immunohistochemistry has revealed the presence of PN-1 in the olfactory mucosa and in the nerve fiber layer of the olfactory bulb. The present electron-microscopic study of the gerbil olfactory bulb confirms the occurrence of PN-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Its expression is finely regulated both spatially and temporally during development and in adulthood (Mansuy et al, 1993). In vivo, PN-1 regulates proteolytic activity in both the CNS and PNS (Monard et al, 1992;Scotti et al, 1994). PN-1 expression has also been detected in rat aortic smooth muscle cells (Richard et al, 2004) and mouse vessels (M. M. Lino, unpublished data).…”
Section: Introductionmentioning
confidence: 89%
“…Its expression is finely regulated both spatially and temporally during development and in adulthood (Mansuy et al, 1993). In vivo, PN-1 regulates proteolytic activity in both the CNS and PNS (Monard et al, 1992;Scotti et al, 1994). PN-1 expression has also been detected in rat aortic smooth muscle cells (Richard et al, 2004) and mouse vessels (M. M. Lino, unpublished data).…”
Section: Introductionmentioning
confidence: 89%
“…The olfactory-globular tract links the terminal medulla and hemiellipsoid body with the olfactory and accessory lobes in the deutocerebrum. nexin, may promote the maturation, maintenance, and turnover of ORNs (Reinhard et al, 1988(Reinhard et al, , 1994Scotti et al, 1994). Glia-derived nexin is similar to serine proteases in the lobster's olfactory organ in that it is produced primarily in non-neural cells and later associates with neurons.…”
Section: Serine Protease Inhibitorsmentioning
confidence: 97%
“…Serine proteases may play a role in the function of glia in the development of the mammalian olfactory epithelium. For example, glia in the olfactory epithelium contain serine proteases, such as the kexin family protease (Akamatsu et al, 1997) and MSP (Scarisbrick et al, 2001), and serine protease inhibitors, such as gliaderived nexin (GDN) (Reinhard et al, 1988;Scotti et al, 1994), which are suspected of being involved in neurogenesis, axogenesis, maturation, and maintenance of ORNs.…”
Section: The Role Of Glia In Sensory Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…OECs also express 3-phosphoglycerate dehydrogenase (Yamasaki et al, 2001), which is a key enzyme in the synthesis of L-serine; it was suggested by Yamasaki et al (2001) that the L-serine made by OECs could be supplied to immature neurons (e.g., newly formed olfactory receptor neurons) in support of local membrane synthesis. Both OECs and astrocytes within the NFL of the olfactory bulb also express protease nexin-1 (PN-1; Reinhard et al, 1988;Scotti et al, 1994), whereas astrocytes elsewhere in the CNS do not express this enzyme. PN-1 has been demonstrated to function as a chemotropic factor for neurites in vitro (Monard et al, 1973;Guenther et al, 1985;Zurn et al, 1988) and could potentially be functioning in the same manner within the primary olfactory pathway.…”
Section: Oecs Normally Differentiate Into Nonmyelinating Gliamentioning
confidence: 99%